Impact of Financial Crises on Dynamics of Capital Structure: Evidence from Korean Listed Companies - Lyubov Tsoy; Almas Heshmati (Institute of Labor Economics (IZA), 2017)
This study examines the impact of 1997 Asian and 2008 Global financial crises on the capital structure of Korean listed companies. Using a data set covering 1,159 Korean listed non-financial firms from 10 industrial sectors over period 1985-2015, the pattern of firms' capital structure before and after the crises is investigated and the speed of adjustment toward the optimal leverage identified. Different effects of the two crises on both capital structure and its adjustment speed is found. The average debt ratio fell significantly, the distance between optimal and observed debt ratios shrank, while the speed of adjustment increased twofold after the Asian crisis. Unlike the Asian crisis, the Global crisis of 2008 had a positive effect on companies' debt ratio and the speed of their adjustment toward optimal leverage. The empirical analysis revealed that Korean non-financial listed companies on average decreased their debt ratios over the entire study period, with leverage being highest before the Asian crisis and lowest after the Global financial crisis. The results also show that the debt ratio of Korean chaebols is higher than that of non-chaebols. Moreover, the high level of leverage is associated with tangible assets, income variability, size and age of the firm, non-debt tax shield, and uniqueness.
Keywords: C33; D21; C51; E22; G32; 330; capital structure; optimal leverage; speed of adjustment; Korean listed companies; financial crises; chaebols